Kris_study
New member
- Joined
- Nov 14, 2020
- Messages
- 3
For us to check your work - you need to share your work. How did you try to solve the problem?I have passed this quiz and need to move on with my life, but I can't let go ofView attachment 23140 this question.
I have google calculated it but I just don't see how to get the answer!
Does anyone get this one easily? Can you explain it?
To Kris_study, Do you know the correct answer or not?I have passed this quiz and need to move on with my life, but I can't let go of this question.
Did you apply the Pythagorean theorem?I have passed this quiz and need to move on with my life, but I can't let go ofView attachment 23140 this question.
I have google calculated it but I just don't see how to get the answer!
Does anyone get this one easily? Can you explain it?
UseHello. Thank you for replying.
No, I don't know which one is the correct answer.
I tried this:
c^2 = (a^2-b^2)^2 + (2ab)^2
a = (2ab)^2 = 4a^2b^2
b = (a^2-b^2)(a^2-b^2) = a^4 -(a^2 b^2) -(b^2 a^2) +b^4
b = a^4 -2(a^2b^2) + b^4
c^2 = a^4 - 2a^2b^2 + b^4 + 4a^2b^2
c = /a^4 + b^4 + 2a^2b^2
Which doesn't match any of the options. So I guessed 1 and was wrong.
I am not really sure how to tackle this question.
You want to find c so why are you solving for a and b?Hello. Thank you for replying.
No, I don't know which one is the correct answer.
I tried this:
c^2 = (a^2-b^2)^2 + (2ab)^2
a = (2ab)^2 = 4a^2b^2
b = (a^2-b^2)(a^2-b^2) = a^4 -(a^2 b^2) -(b^2 a^2) +b^4
b = a^4 -2(a^2b^2) + b^4
c^2 = a^4 - 2a^2b^2 + b^4 + 4a^2b^2
c = /a^4 + b^4 + 2a^2b^2
Which doesn't match any of the options. So I guessed 1 and was wrong.
I am not really sure how to tackle this question.
Use
a^4 + b^4 + 2a^2b^2 = (a^2 + b^2)^2